Challenges and difficulties in implementing and adopting isolation and quarantine measures among internally displaced people during the COVID-19 pandemic in Mali (161/250) - Birama Apho Ly; Mohamed Ali AG Ahmed; Fatoumata Bintou Traore; Niélé Hawa Diarra; Mahamadou Dembele; Djeneba Diarra; Inna Fatoumata Kandé; Hamadoun Sangho; Seydou Doumbia (Elsevier, 2022)
Introduction: Isolation and quarantine are among the key measures that protect internally displaced people (IDPs) against COVID-19. This study aims to identify the challenges encountered by humanitarian actors, and health, political, and administrative stakeholders in implementing these measures. It also describes the difficulties faced by IDPs when adopting them, and the local initiatives developed to overcome those difficulties. Method: We conducted a qualitative survey consisting of individual interviews and focus groups among IDPs, humanitarian actors, and health, political, and administrative stakeholders. The data was collected between November and December 2020 in the Bamako and Ségou Regions of Mali. Interviews were recorded with audio recorders, then transcribed and thematically analyzed using the NVivo 13 software. Findings: The study involved 36 individual interviews and eight focus groups with 68 participants of whom IDPs represented 72.3%. The main challenges reported on IDP sites included difficulties in contacting positive cases, a lack of facilities for quarantine and isolation, a lack of physical space for building new facilities, and a lack of financial resources to support IDPs during isolation and quarantine. The difficulties reported included: changes in social behavior and practices, fear of stigma, a poor level of literacy, and language barriers. To address those difficulties, the local initiatives developed by IDPs included strengthening the awareness of IDPs on COVID-19, early warning of sites' leaders about positive and suspected cases, and setting up a toll-free number to facilitate access to appropriate information on COVID-19. Conclusion: The findings of this study could be used as evidence to guide policy, adjust current strategies and take into account with more focus IDPs, a group with increased vulnerability, in COVID-19 response, more precisely during the implementation of isolation and quarantine measures. By doing so, they will help improve the response to COVID-19, IDPs health, and population health.